2019
DOI: 10.1108/qrfm-08-2017-0073
|View full text |Cite
|
Sign up to set email alerts
|

Groups, social processes and decision making in finance

Abstract: Purpose This paper aims to investigate a double puzzle, empirical and theoretical. Empirically, can the authors document the influence of groups on financial decisions in investments and trading? Theoretically, if decisions in a group context can be documented, how can we account for them, against the background of the normative models, according to which financial decisions are individualized and atomized? Based on interviews and ethnographic observations with fund managers, analysts and traders, the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Montier's taxonomy itself, which is the basis of the present study, has identified social interaction and transmission of information across social groups as a potential source of bias (Montier, 2002). Scholars have also argued that, in the future, the individual decision‐making process might be better understood by evaluating group decision‐making processes (Preda & Muradoglu, 2019). Recommendation intentions are particularly important to understand in the case of millennials as they represent generational cohorts exposed to information technology at a young age (Chen & Howard, 2020), which enables them to stay connected with others.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Montier's taxonomy itself, which is the basis of the present study, has identified social interaction and transmission of information across social groups as a potential source of bias (Montier, 2002). Scholars have also argued that, in the future, the individual decision‐making process might be better understood by evaluating group decision‐making processes (Preda & Muradoglu, 2019). Recommendation intentions are particularly important to understand in the case of millennials as they represent generational cohorts exposed to information technology at a young age (Chen & Howard, 2020), which enables them to stay connected with others.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Despite the traditional view that returns increase in leverage under strict assumptions of rationality and returns reflecting compensation for risk we provided empirical evidence that they in fact decrease in leverage (Muradoglu and Sivaprasad, 2010, 2012). Actual decision-making processes among professionals and individuals are alike in that they can be understood as group decision-making processes and can be studied as such (Preda and Muradoglu, 2019). Maybe in the future all assumptions about individual decision making processes will be replaced with ones about group decision-making (Preda and Muradoglu, 2019).…”
Section: Gulnur Muradoglu's Route Into Behavioural Financementioning
confidence: 99%
“…Actual decision-making processes among professionals and individuals are alike in that they can be understood as group decision-making processes and can be studied as such (Preda and Muradoglu, 2019). Maybe in the future all assumptions about individual decision making processes will be replaced with ones about group decision-making (Preda and Muradoglu, 2019).…”
Section: Gulnur Muradoglu's Route Into Behavioural Financementioning
confidence: 99%
“…The financial aspect of dissemination of smart technologies is studied in the works Aisaiti et al (2019), Burger-Helmchen et al (2020, Preda and Muradoglu (2019), and Zhang et al (2019). Thus, the problem of financing of public-private partnership projects based on smart technologies has been studied fragmentarilythere is a clear emphasis on financing of digital modernization based on the mechanism of publicprivate partnership, while digitalization of the process of public-private partnership and its financing remains poorly studied.…”
Section: Methodsmentioning
confidence: 99%